Implementation and Operational Research: The Effectiveness of Routine Opt-Out HIV Testing for Children in Harare, Zimbabwe. (1st January 2016) - Ferrand, Rashida Abbas; Meghji, Jamilah; Kidia, Khameer; Dauya, Ethel; Bandason, Tsitsi; Mujuru, Hilda; Ncube, Getrude; Mungofa, Stanley; Kranzer, Katharina
Abstract : Objective: HIV testing is the entry point to access HIV care. For HIV-infected children who survive infancy undiagnosed, diagnosis usually occurs on presentation to health care services. We investigated the effectiveness of routine opt-out HIV testing (ROOT) compared with conventional opt-in provider-initiated testing and counseling (PITC) for children attending primary care clinics. Methods: After an evaluation of PITC services for children aged 6–15 years in 6 primary health care facilities in Harare, Zimbabwe, ROOT was introduced through a combination of interventions. The change in the proportion of eligible children offered and receiving HIV tests, reasons for not testing, and yield of HIV-positive diagnoses were compared between the 2 HIV testing strategies. Adjusted risk ratios for having an HIV test in the ROOT compared with the PITC period were calculated. Results: There were 2831 and 7842 children eligible for HIV testing before and after the introduction of ROOT. The proportion of eligible children offered testing increased from 76% to 93% and test uptake improved from 71% to 95% in the ROOT compared with the PITC period. The yield of HIV diagnoses increased from 2.9% to 4.5%, and a child attending the clinics post intervention had a 1.99 increased adjusted risk (95% CI: 1.85 to 2.14) of receiving an HIV test in the ROOT period compared with the preintervention period. Conclusion: ROOT increased the proportion of children undergoing HIV testing, resulting in an overall increased yield of positive diagnoses, compared with PITC. ROOT provides an effective approach to reduce missed HIV diagnosis in this age group.